2022
DOI: 10.1111/jerd.12958
|View full text |Cite
|
Sign up to set email alerts
|

Study on the surface properties of different commercially available CAD/CAM materials for implant‐supported restorations

Abstract: Objective: To determine if there are any differences in surface characteristics (surface roughness and contact angle) among different CAD/CAM materials indicated for fabricating implant-supported restorations, following all the material preparation protocols provided by the manufacturer.Materials and Methods: One-hundred forty-four specimens were divided into six groups: RBC (resin-based composite), PMMA (polymethyl methacrylate), PEEK (polyether ether ketone), ZP (zirconia polished), ZG (zirconia glazed) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The surface roughness of dental materials is extremely important, as it influences microbial adhesion, biocompatibility, wear, corrosion behavior, and esthetics [ 25 ]. Reduced surface irregularities play a significant function in improving tongue sensation and in preventing dental plaque from adhering to dental prosthetics.…”
Section: Characteristics Of Peek and Its Composite Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface roughness of dental materials is extremely important, as it influences microbial adhesion, biocompatibility, wear, corrosion behavior, and esthetics [ 25 ]. Reduced surface irregularities play a significant function in improving tongue sensation and in preventing dental plaque from adhering to dental prosthetics.…”
Section: Characteristics Of Peek and Its Composite Materialsmentioning
confidence: 99%
“…Previous research [ 28 ] reported that PEEK discs showed significantly higher nano-roughness than machined titanium ( p = 0.005). For other materials, in vitro research [ 25 ] comparing PEEK and other CAD/CAM materials showed that samples of PEEK were slightly rougher than samples of polymethyl methacrylate (PMMA) and resin-based composites. The reason for this could be related to the ceramic particles added to PEEK [ 25 , 29 ].…”
Section: Characteristics Of Peek and Its Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cylinder-shaped specimens, with 5 mm diameter and 2 mm thickness, were obtained for each of the three materials: ZR (zirconia), PEEK (polyether ether ketone) and CoCr 4 (CoCr 4 alloy). The complete preparation, finishing and polishing procedure of all specimens was completed by one operator, strictly following manufacturer's recommendation, as described in our previous research [17]. Prepared specimens were cleaned in an ultrasonic bath (BK-3A Ultrasonic cleaner; Baku), in 70% ethanol for 5 min and distilled water for another 5 min.…”
Section: Preparation Of the Specimensmentioning
confidence: 99%
“…Therefore, the first null hypothesis is rejected. The fact that during the glazing procedure technician manually apply the glaze layer with the brush onto the material's surface could be the best explanation for these results [30]. In addition, the glazed surface is rich with bubbles, which leads to the impossibility to create a surface as smooth as when finishing the material's surface using burs and rubbers [22].…”
Section: Mechanicalmentioning
confidence: 99%